Patient-specific thoracic endovascular aoratic repair (TEVAR) - Lin, Andrew (Department of Human Biology, 2020)
Endovascular aortic repair (EVAR) is a minimally invasive procedure to treat aortic aneurysms. Current off-the-shelf devices may not fit the patient perfectly, potentially increasing the chance of post-operative complications. This project aims to provide proof of concept for rapidly creating inexpensive patient-specific EVAR stent-grafts, conforming to the unique anatomy of the patient. After investigating the range of electrospinning shape capabilities on idealised stent-graft geometries (straight, tapered, elliptical, and curved), CT scans was used to create blood and aortic models of an abdominal aortic aneurysm. The former was used to design a patientspecific stent-graft geometry, 3D print a conductive electrospinning mandrel, and electrospin (290 mm, +18 kV, -3 kV, 5 ml/hr, 5 mm/s, 750 rpm) Polyurethane (PU). Sinusoidal Nitinol reinforcement segments were subsequently incorporated into the graft. Various geometries were successfully spun. Electrospun PU scaffolds had a mean ultimate tensile strength of 7.3 MPa, mean Young’s Modulus of 1.9 MPa, and a mean maximum strain of 571%. Fibre morphology analysis showed a mean orientation index of 0.25 (750 rpm) and 0.35 (1000 rpm), mean fibre diameter of 2.3 µm, and a mean pore size of 7.5 µm; pore size indicates possibility of endothelialisation. Nitinol reinforced patient-specific graft was successfully made and stent-grafts of various stent patterns had radial forces between 1.3 to 5.8 N (comparable to 2.8 N from a commercial example). FEA simulation highlighted various advantages of customised stent-grafts that conform to the anatomy over standard cylindrical devices such as better seal and contact traction. Simulation results (25 mm Ø, cylindrical, electrospun stent-graft) showed close approximations to experimental results; its use for future stent-graft design optimisations is promising. Mock insertion of an electrospun patient-specific stent-graft was performed in a 3D-printed transparent-PLA hollow aortic model with good conformity, albeit subpar visibility without a backlight and inflexibility. Although further improvements can be made to the individual steps, proof of principle was achieved. This process is very promising for the manufacturing of patient-specific devices that could offer better long term outcomes.